Novel organometallic compounds for cancer treatment - Zhanbossinova, A.; Yespolayeva, S.; Khamitova, G.; Negmetzhanov, B.; Alibek, K.; Adilov, S. (Nazarbayev University, 2013)
Incorporating indole, resorcinol, and porphyrin derivatives into ferrocene and ruthenium complexes could improve their anticancer activity. These compounds are furnished with functional groups which are expected to induce programmed cell death and show high selectivity to cancer cells. Currently, they are at the stage of in vitro testing for anticancer activity.
Keywords: first research week; cancer treatment; anticancer activity